2011
DOI: 10.1017/s0022029911000641
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of milk fatty acids based on genetic and herd parameters

Abstract: The objective of this study was to characterize the fatty acids (FA) in milk based on genetic and herd parameters to investigate the origin of the different FA in milk. Milk samples of 1912 Dutch HolsteinFriesian cows were analysed for 39 different FA including odd and branched-chain fatty acids. The proportion of variation caused by genetic and herd effects was calculated. In addition, genetic and herd correlations among the fatty acids were estimated and a clustering technique was used to visualise these cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
6
22
0
Order By: Relevance
“…A total of 47 individual fatty acids, 13 groups of fatty acids, and 5 desaturation indices were evaluated. The phenotypic variations observed for the milk yield, milk fat content, and relative proportions of individual fatty acids (Table 1) are in line with the results from previous studies in Holstein cows (Moate et al, 2007;Bobe et al 2008;Heck et al, 2012) and other breeds, including Brown Swiss (Kelsey et al, 2003;Soyeurt et al, 2007;Vlaeminck et al, 2006). Likewise, the relative proportions of the SFA, MUFA, PUFA, and stearoyl-CoA desaturase (SCD) indices (Table 2) were consistent with data previously reported by Soyeurt et al (2006) and Garnsworthy et al (2010).…”
Section: Milk Fatty Acid Profile Of Brown Swiss Cowssupporting
confidence: 92%
See 2 more Smart Citations
“…A total of 47 individual fatty acids, 13 groups of fatty acids, and 5 desaturation indices were evaluated. The phenotypic variations observed for the milk yield, milk fat content, and relative proportions of individual fatty acids (Table 1) are in line with the results from previous studies in Holstein cows (Moate et al, 2007;Bobe et al 2008;Heck et al, 2012) and other breeds, including Brown Swiss (Kelsey et al, 2003;Soyeurt et al, 2007;Vlaeminck et al, 2006). Likewise, the relative proportions of the SFA, MUFA, PUFA, and stearoyl-CoA desaturase (SCD) indices (Table 2) were consistent with data previously reported by Soyeurt et al (2006) and Garnsworthy et al (2010).…”
Section: Milk Fatty Acid Profile Of Brown Swiss Cowssupporting
confidence: 92%
“…High herd-date effects and low heritability estimates were also found for odd-chain fatty acids and BCFA (Table 3), which is consistent with the existing literature (Vlaeminck et al, 2006;Patel et al, 2013). A previous study showed that the herd-date also strongly influenced LCFA, trans fatty acids, C18:1 trans-11 (VA), and C18:2 cis-9,trans-11 (RA), likely reflecting the effect of dietary factors on the contents of these fatty acids in milk fat (Heck et al, 2012). In Holstein cattle, high herd-date effects were reported for VA and RA (Stoop et al, 2008;Duchemin et al 2013), and the heritability estimates for VA and RA ranged from null to bigger than 0.4 (Bobe et al, 2008, Stoop et al, 2008Mele et al, 2009).…”
Section: Heritability and Herd-date Effect For Milk Fatty Acid Profilesupporting
confidence: 90%
See 1 more Smart Citation
“…But Heck et al (2012) suggested that a part of these two FAs derives from the blood, meaning that the influence of animal’s diet also is of importance. Similarities between IC and RCC also agree with this as they were on the same diet.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genetic and herd clustering of milk FA, Heck et al (2012) found that C4:0 and C12:0 differed from the general pattern of the other FA in the group of de novo synthesized even-chain FA. Milk FA C12:0 and C14:0 are not only synthesized de novo in the mammary gland, but can also originate from dietary C12:0 and C14:0 (e.g., van Zijderveld et al, 2011b).…”
Section: Random-effects Model Analysis Correlation Per Unit Of Feedmentioning
confidence: 96%